The Relationship Between Body Mass Index and Diabetic Neuropathy in Patients With Diabetes Mellitus at the Regional General Hospital dr.Soehadi Prijonegoro Sragen District - Berlyna Mey Anggraini; Okti Sri Purwanti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Diabetic neuropathy is a prevalent consequence of diabetes mellitus, affecting around 50% of individuals with the condition. There exists a strong correlation between the onset of diabetic neuropathy and body mass index. There is a positive correlation between body mass index and the risk of neuropathy. The objective of this study is to investigate the correlation between body mass index and diabetic neuropathy among individuals diagnosed with diabetes mellitus within the context of dr. Soehadi Prijonegoro Sragen Regional General Hospital. The present study employed quantitative methodologies with a cross-sectional design. The present investigation was carried out under the operational jurisdiction of the Regional General Hospital dr. Soehadi Prijonegoro Sragen. The study's implementation commenced in September 2023 and concluded in February 2024. A total of 782 patients diagnosed with diabetes mellitus were included in the study population at dr. Soehadi Prijonegoro Sragen Regional General Hospital. A purposive sampling strategy was used to choose a sample of 89 people with diabetes mellitus for this investigation. The study examined the relationship between the independent variable, Body Mass Index, and the dependent variable, diabetic neuropathy. The study employed a research instrument in the form of a questionnaire administered through direct interviews. Data collection was carried out using weight scales using Speeds brand digital weight scales and Stature Meter to measure height. Diabetic neuropathy measurement instrument using diabetes neuropathy symptom score (DNS). Data analysis using bivariate analysis with chi-square test, data processing with SPSS software version 20. The results showed that there was a significant relationship between body mass index and the incidence of diabetic neuropathy in patients with diabetes mellitus at dr. Soehadi Prijonegoro Sragen Regional General Hospital (p-value=0.032). Keyword: Body Mass Index, Diabetic Neuropathy, Diabetes Mellitus